RESEARCH ARTICLE: “The Sea Being Without the Common Law”: The Civil Law Tradition, the Law of Nations, and Maritime Jurisdiction in British Newfoundland to 1849 - Post, Andy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2025)
Historians’ traditional assumption that British Newfoundland’s legal history is best explained through the lens of English common law fails to account for English and Anglo-American historic legal pluralism, leaving the civil law’s role in colonial state formation altogether unexplored. In medieval, early modern, and late modern England, the civil law, based on Roman law rather than the “common” law of municipal courts, was the law of international, maritime, commercial, and military matters. When “English Newfoundland” emerged from a multinational, mixed society of settlers and fishers, asserting the Crown’s jurisdiction both on land and at sea, over foreign nationals as well as British subjects became essential — as the Piracy Acts, the Navigation Acts, local reforms, and international treaties increased the importance of British maritime jurisdiction. Until the constitutional crisis of 1789–93, apparent shifts toward a “common-law system” tended to increase civil-law courts’ jurisdictions and personnel. While the Court of Vice-Admiralty in St. John’s was abolished in 1824, the civil law survived in the Supreme Court’s “admiralty” jurisdiction — belying that tradition’s earlier importance. This article explores the rise and fall of the civil law in British Newfoundland to the repeal of the Navigation Acts in 1849.